The effect of pulse-like ground motion on the performance-based confidence level of setback special steel moment-resisting frames. (December 2021) - Homaei, Farshad; Mashhadi, Sima
Abstract: This paper addresses the effects of near-fault (NF) earthquake records containing forward directivity pulses and the pulse-to-structure period ratio ( T P /T 1 ) on the performance-based confidence levels of regular and setback frames. For this purpose, ten steel moment-resisting frames, including a regular structure and nine setback frames, were subjected to 55 near-fault pulse-like records as well as their low- and high-frequency components called the "pulse" and "residual" portions, respectively. To study the effect of the T P /T 1 ratio, the records were classified into four groups representing average values of T P /T 1 ∼ 0.5, 1, 2, and >2. In addition to NF motions, 32 far-fault records were imposed on the studied structures. The results from incremental dynamic analyses revealed the higher confidence level of meeting performance levels under NF records compared to far-fault ones for both regular and setback frames (the case of T P /T 1 ≥1 for the regular frame and the cases of T P /T 1 ∼ 1 and 2 for the irregular ones). The importance of considering the T P /T 1 ratio was shown by comparing the performance-based confidence levels under FF and NF ground motions as well as those under original NF records and their frequency components. It was found that ignoring such classification can lead to reversed results for both regular and irregular structures. Furthermore, directivity pulses with T P /T 1 >1 can represent original NF records when evaluating the confidence levels of the regular structures, especially as LS and CP limit states. However, it is highly recommended to impose original NF records on irregular structures to assess their performance-based confidence levels. Highlights: The performance-based confidence level of setback special steel moment-resisting frames is assessed. The role of the ground motion type (i.e., the near- or far-fault) on the structural level of confidence is addressed. The importance of the pulse-to-structure period ratio ( T P /T 1 ) on the performance-based confidence level of structures is evaluated. The contribution of the frequency components of near-fault records to the performance-based confidence levels is assessed.